2020
DOI: 10.1093/scan/nsaa118
|View full text |Cite
|
Sign up to set email alerts
|

Concordance in parent and offspring cortico-basal ganglia white matter connectivity varies by parental history of major depressive disorder and early parental care

Abstract: Social behavior is transmitted cross-generationally through coordinated behavior within attachment bonds. Parental depression and poor parental care are major risks for disruptions of such coordination and are associated with offspring’s psychopathology and interpersonal dysfunction. Given the key role of the cortico-basal ganglia/(CBG) circuits in social communication, we examined similarities (concordance) of parent-offspring CBG white-matter/(WM) connections and how parental history of major depressive diso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 124 publications
(160 reference statements)
1
13
0
Order By: Relevance
“…Our finding, in concert with those of previous studies, confirms the role of social support in promoting physical and psychological health and overall wellbeing to the individual and offspring across the life span (Pierce et al, 1996). In addition, this finding is consistent with previous animal and human studies highlighting the social buffering effect across the life span (Gunnar & Hostinar, 2015) and showing that social attachments, including pair bonding, friendship, and family bonds, have been found to moderate both genetic and environmental vulnerabilities and confer resilience to stress and adversity (Abraham et al, 2020;Feldman, 2020;Levy & Feldman, 2019;Schury et al, 2017;Vakrat, Apter-Levy, & Feldman, 2018).…”
Section: Four Important Aspects Of the Intergenerational Transmission...supporting
confidence: 91%
“…Our finding, in concert with those of previous studies, confirms the role of social support in promoting physical and psychological health and overall wellbeing to the individual and offspring across the life span (Pierce et al, 1996). In addition, this finding is consistent with previous animal and human studies highlighting the social buffering effect across the life span (Gunnar & Hostinar, 2015) and showing that social attachments, including pair bonding, friendship, and family bonds, have been found to moderate both genetic and environmental vulnerabilities and confer resilience to stress and adversity (Abraham et al, 2020;Feldman, 2020;Levy & Feldman, 2019;Schury et al, 2017;Vakrat, Apter-Levy, & Feldman, 2018).…”
Section: Four Important Aspects Of the Intergenerational Transmission...supporting
confidence: 91%
“…Intergenerational neuroimaging combines successful features of existing research designs (e.g., family studies, concordance models) to further knowledge of mechanisms promoting brain development. The first studies directly investigating structural and functional brain similarity in parent-child dyads mostly focused on affective ( Yamagata et al, 2016 , Foland-Ross et al, 2015 , Abraham et al, 2020 , Colich et al, 2017 , Wang et al, 2018 ) or cognitive trait transmission ( Vandermosten et al, 2020 , Takagi et al, 2021 ). For example, Foland-Ross and colleagues reported on structural brain similarity by means of cortical thickness in mother-child dyads with and without a history of depression ( Foland-Ross et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that OT administration increased social affiliation and reduced CT levels (Brown et al., 2016; Ditzen et al., 2009; Meinlschmidt & Heim, 2007), and buffered CT responses to stress in adults with impaired emotion regulation abilities (Quirin et al., 2011). Parent‐child synchrony and the OT system are shaped during the transition to parenthood and carry long‐term effects on child's brain, behavior, and psychopathology (Abraham et al., 2020), hence are defined as markers of resilience and are related to child's greater adaptation in the context of adversity (Feldman, 2020).…”
Section: Introductionmentioning
confidence: 99%